Monitoring of the Bond State between the Concrete-Filled Steel Tube Pile and Surrounding Soil - Daopei Zhu; Yali Hu; Cai Wu (Shock and Vibration)
The bonding state of the pile-soil interaction is complex. Traditional monitoring methods and tools have not been fully applied to monitor and evaluate it although it affects the lifecycle safety of the pile. In this study, a health monitoring method is proposed to evaluate the bonding state of the pile-soil contact area; it is a transient impact response method based on piezoelectric ceramic sensors to monitor the pile-soil bonding state. During the test, different damage degrees of the pile-soil bonding state were simulated by considering the working conditions of different soil densities and different crack depths as examples. A horizontal transient impact stress was applied to the pile top, and a piezoelectric ceramic sensor embedded in the pile detected the stress wave. As the stress wave response differs in different damage conditions, an energy index was established to quantitatively monitor the degree of damage.